Evaluasi Usaha Pembudidayaan Ikan di Desa Matungkas Kabupaten Minahasa Utara - Koten, Elias; Mondoringin, Lukas L.J.J; Salindeho, Indra R.N (e-Journal BUDIDAYA PERAIRAN, 2015)
The purppuse of research was to study the feasibility of fish culture technically and economically.  Primary data was gathered by interview to fish farmer and secondary data was obtained from related references.  Data analyzed were break even point and foof conversion ratio.  Water source of pond was spring water and the pond depth was 0.50 – 1.75 m.  Juveniles were obtained fron Tatelu Freshwater Aquaculture Board  and other palces.  Fish was fedr pellet for 3-4 months. Pond conctruction did not match the criteria . Fish farmer did not used capital from bank and farmers did not use book account in running the business. Food conversion ratio was 2.5 – 3.5. The price of pellet was Rp. 8.500/kg ang fish price was Rp. 25.000/kg.  Fish farmer dit not receive enough profit in running fish culture   Keywords:  feasibility study, pond construction, fish culture, Matungkas Village